“Anyone who weighs up risks doesn’t belong here”: how do elite handball players manage physical health risk throughout their professional careers? - Bursik, Jan; Mayer, Jochen; Thiel, Ansgar; Kühnle, Felix; John, Jannika M. (Frontiers in Sports and Active Living, 2025)
ObjectivesElite athletes frequently encounter physical health risks, such as an injury, illness or pain, which are accompanied by sociocultural norms, individual perceptions, and situational pressures. While research has explored risk management in sports, limited attention has been given to the subjective experiences of athletes managing these risks across their careers. This study addresses this gap by examining how elite handball players manage physical health risks, focusing on the role of risk perception, evaluation, and coping.MethodsUsing a constructivist lens, 11 handball players from the German national teams (5 females, 6 males) participated in biographical mapping interviews, providing insights into their career-long management of physical health risks.ResultsUsing reflexive thematic analysis, we generated four themes: (1) Externalizing risks and refraining from proactivity, (2) Relinquishing control under medical uncertainty, (3) Fluctuating prioritization of health or success, and (4) Calculated health-risk taking to achieve success. The findings illustrate that athletes’ risk management strategies vary based on career stage, injury experiences, situational priorities, and social pressures. The insights contribute to a deeper understanding of the dynamics of physical health risk management in high-performance sports and their sociocultural underpinnings. The study highlights the need for interventions that foster proactive risk management, emphasize personal agency, and balance performance with long-term health.